Teacher Identity in English Medium Instruction Schools of Nepal - Ghimire, Nanibabu (Journal of NELTA Gandaki, 2021)
A large number of community schools in Nepal are shifting their medium of instruction policy from Nepali to English. This shift to English as a Medium of Instruction (EMI) has the potential for disruption and changes in teachers’ perception of their own identities. The main purpose of the study was to investigate how teachers’ perception of their own identity is shaped and re-shaped along with the changing landscape of medium-of-instruction policy in Nepal’s community schools. Following narrative inquiry research design, I conducted semi-structured interviews with three primary teachers from three EMI community schools which were purposively selected. As the findings revealed, the EMI policy overhaul has created two opposing sets of new identities of teachers: on the one hand, there is admiration among the general public towards English as a linguistic capital in Nepal and it has become a part of the linguistic identity of teachers as they are being responsible, laborious, punctual, dedicated, and regular for effective teaching and learning, on the other hand, they cannot explore the content in English in comparison to Nepali since they are not trained as well as equipped with the facilities that are needed to EMI.